Sharia Based Psychosocial Counselling Model for Single Mothers: Model Pendampingan Psikososial Berbasis Syariah untuk Ibu Tunggal - Abdul Rahman Ramadhan (Syamilah Publisher, 2025)
The increasing number of single mothers in Indonesia has become a significant concern in family law studies, especially in the context of psychosocial issues they face. Single mothers often encounter various psychological stressors, including economic, social, and psychological stress. This study explores the effectiveness of a Sharia-based psychosocial counseling model for single mothers to address these challenges. The research employs a qualitative approach, involving a comprehensive review of relevant literature and secondary data to examine the role of Sharia principles in enhancing mental resilience, financial management, and social support. The results suggest that integrating Sharia principles in counseling provides not only psychological support but also spiritual guidance that empowers single mothers to overcome life's challenges. Programs that incorporate financial education, emotional resilience training, and community support can significantly reduce stress and improve their overall well-being. This study contributes to understanding how Sharia-based psychosocial counseling can be adapted to meet the needs of single mothers in contemporary society, promoting both mental health and social inclusion.